Profil Model Berpikir Mahasiswa Dalam Menyelesaikan Persoalan Logika Matematika Dan Teori Himpunan - Putra, Dewa Putu Wiadnyana (Jurnal Pendidikan Matematika RAFA, 2021)
This research aims to 1) determine the profiles of students 'thinking models and 2) describe the relationship between students' thinking models in solving mathematical logic problems and set theory. This research is a descriptive study. The instrument used was a test consisting of 3 stages. The targets of the thinking models in the given tests are 1) Arithmetic, 2) Geometric, 3) Abstract, 4) Arithmetic-Geometric, 5) Geometric-Abstract, and 6) Arithmetic-Abstract. The results of this research are 1) the dominance of arithmetic thinking models (72.3%) in the early stages is higher than geometric (60.7%) and abstract (45.7%) thinking models. In the stage II and III tests, there was an increase in abstract thinking skills to 54.6% and 60.2%, respectively. 2) The relationship between thinking models can be identified in stage II and III tests. Arithmetic-Geometric relationships are used in situation modeling and procedural analysis of problems. Geometric-Abstract relationships are used in constructing formal concepts of intusion in cognitive structures. Arithmetic-Abstract relationships are used in generalized patterns and formal proof.